Komunikasi Magis Dukun (Studi Fenomenologi Tentang Kompetensi Komunikasi Dukun) - Ali Nurdin (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
This study departs from the rampant phenomenon of people believe and go shaman. Shamans believed to have the ability and expertise to provide suggestions in the process of healing and helping people. The problem in this study is how the experience, skills and expertise shaman in Lamongan in his work treating and helping the client? The purpose of this study was to understand and explore in depth the communication competence magical shaman related to his work in serving and treating clients in Lamongan East Java Province. This study used a phenomenological approach to qualitative research methods The subjects in this study were shamans and existing clients in the area of Lamongan East Java Province. Data sources or selected informants purposively with the terms directly experience the events that are the focus of research, able to recount events that happened, and be willing to research informants. Data collection techniques in this study using the technique of interviewing, observation, and document review. While the data analysis techniques used in this study are three flow activities: data reduction, data presentation, and conclusion / verification. The results of this study describes the capabilities and expertise of shaman is suwuk, petungan, penerawangan, and prewangan. Ability and skills possessed shaman on that gave birth a new communication concept is suwuk communication, petungan communication, penerawangan communication, and prewangan communication.